Whitewashed : America's invisible Middle Eastern minority - Tehranian, John (New York University Press, 2009)
Middle Easterners: Sometimes White, Sometimes Not - an article by John Tehranian. The Middle Eastern question lies at the heart of the most pressing issues of our time: the war in Iraq and on terrorism, the growing tension between preservation of our national security and protection of our civil rights, and the debate over immigration, assimilation, and our national identity. Yet paradoxically, little attention is focused on our domestic Middle Eastern population and its place in American society. Unlike many other racial minorities in our country, Middle Eastern Americans have faced rising, r.
Keywords: Arab Americans -- Social conditions.; Iranian Americans -- Social conditions.; Turkish Americans -- Social conditions.; Arab Americans -- Legal status, laws, etc.; Iranian Americans -- Legal status, laws, etc.; Turkish Americans -- Legal status, laws, etc.; White people -- Race identity -- United States.; Racism -- United States.; Race discrimination -- United States.; United States -- Race relations.; Américains d'origine arabe -- Conditions sociales.; Américains d'origine iranienne -- Conditions sociales.; Américains d'origine turque -- Conditions sociales.; Racisme -- États-Unis.; États-Unis -- Relations raciales.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Arab Americans -- Social conditions; Iranian Americans -- Social conditions; Race discrimination; Race relations; Racism; White people -- Race identity; United States